Potassium fertilization and irrigation with treated wastewater on gas exchange of colored cotton - Breno L. de C. Lima; Ênio F. de F. e Silva; Hugo R. B. Santos; Edivan R. de Souza (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of treated domestic wastewater in agriculture is promising because it contains essential nutrients for crops, especially for cotton plants. Information on leaf gas exchanges helps to understand the responses of plants to different water and nutrient managements, since they directly affect physiological processes. Thus, the objective of this study was to evaluate the effect of potassium fertilization and irrigation with treated wastewater on the gas exchange of naturally colored cotton plants grown in the semi-arid region of the state of Pernambuco, Brazil, providing a reference for evaluations of responses of cotton plants to abiotic factors. The experiment was conducted in a randomized block design, in a 5 × 5 factorial arrangement, with four replications. The treatments consisted of five potassium rates (0, 50, 100, 150, and 200% of the recommended rate for the crop) and five irrigation depths (50, 75, 100, 125, and 150% of the evapotranspiration of the crop). The highest stomatal conductance, transpiration, net assimilation rate, intercellular CO2 concentration, and carboxylation efficiency were found in irrigated plants with 110, 99, 117, 150, and 113% of ETc, combined with the potassium rates of 96, 113, 97, 100, and 100% of the recommendation rate for the crop, respectively. The increase in irrigation depths increased the diffusion of CO2 of the plants. The highest instantaneous water-use efficiency was found with the irrigation of 150% of ETc without potassium fertilization. According to the interaction between irrigation depths and potassium rates, the most efficient potassium rate for naturally colored cotton depends on the irrigation depth applied.